2012
DOI: 10.1016/j.fct.2011.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Red meat intake-induced increases in fecal water genotoxicity correlate with pro-carcinogenic gene expression changes in the human colon

Abstract: Red meat consumption is associated with an increased colorectal cancer (CRC) risk, which may be due to an increased endogenous formation of genotoxic N-nitroso compounds (NOCs). To assess the impact of red meat consumption on potential risk factors of CRC, we investigated the effect of a 7-day dietary red meat intervention in human subjects on endogenous NOC formation and fecal water genotoxicity in relation to genome-wide transcriptomic changes induced in colonic tissue. The intervention showed no effect on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 46 publications
4
46
1
Order By: Relevance
“…Recently, human studies have demonstrated that indeed under normal dietary conditions urinary markers of exposure to N-nitroso compounds are associated with micronucleus frequencies, a validated marker of carcinogenic risk, as well as with gene expression changes that are involved in cancer development (Hebels, Jennen, et al, 2011). Similar gene expression changes were also found in colonic biopsy material after a human intervention study with red meat (Hebels, Sveje, et al, 2011;Hebels et al, 2012).…”
Section: N-nitroso Compoundssupporting
confidence: 57%
“…Recently, human studies have demonstrated that indeed under normal dietary conditions urinary markers of exposure to N-nitroso compounds are associated with micronucleus frequencies, a validated marker of carcinogenic risk, as well as with gene expression changes that are involved in cancer development (Hebels, Jennen, et al, 2011). Similar gene expression changes were also found in colonic biopsy material after a human intervention study with red meat (Hebels, Sveje, et al, 2011;Hebels et al, 2012).…”
Section: N-nitroso Compoundssupporting
confidence: 57%
“…Intervention study Applied Biosystems --Virgin olive oil induced the expression of genes associated with atherosclerosis development and progression [120] Mild restriction of food intake Rats Affymetrix DAVID -Long-term energy restriction induced Cyp4A14 and PPARa gene expression [121] Fasting and refeeding Rats Agilent (Cy3, Cy5) Metacore, Ermine J -The expression of the genes involved in energy metabolism was altered by the feeding conditions [122] Rosemary extract K562 cell line Affymetrix IPA -Rosemary extract regulated changes in the expression of genes regulated by Myc transcription factor [123] Kiwifruit extract Mice Agilent (Cy3, Cy5) GSEA -Kiwifruit extract affected the expression of genes involved in immune signaling pathways and metabolic processes in colon [124] Milk and yogurt Intervention study Agilent (Cy3) GenMAPP, MAPPfinder, MetaCore, GSEA -Milk and yogurt down-regulated genes involved in protein biosynthesis and mitochondrial activities at 2 h, whereas opposite kinetics were observed for genes linked to inflammatory and apoptotic processes [125] Red meat Intervention study Agilent (Cy3) MetaCore -High consumption of red meat induced changes in genes involved in DNA damage repair, cell cycle, and apoptosis pathways [126] Rosemary extract HT29/SW480 cell lines Affymetrix IPA, GSEA -Rosemary extract induced the expression of genes that encode antioxidant phase II enzymes [127] realize its full potential in food science. Despite the extraordinary reductions in cost per sequenced base associated with SGS compared with more conventional sequencing methods, the application of RNA-seq to survey the transcriptome (structure and expression levels) is still expensive.…”
Section: Short-and Long-term Caloric Restrictionmentioning
confidence: 98%
“…In this regard, several studies have also been conducted to investigate the potential chemopreventive activities and/or therapeutic effects of dietary compounds on cellular and animal models of disease [123,127]. Similarly, microarray analysis can also be applied to investigate the role of certain food products or diets as potential risk factors for chronic diseases, such as red meat consumption in colorectal cancer [126].…”
Section: Nutrigenomicsmentioning
confidence: 99%
“…Studies in germ-free mice have shown that fewer cancers are formed with chemical carcinogens compared with mice with normal faecal bacteria [31]. Bacteria are capable of forming genotoxic products from normal dietary components, especially meat protein [32]. Information regarding the species and functional composition of the human gut microbiome is limited to data from a handful of cohorts with little evidence regarding variation across the world.…”
Section: Impact Of Diet On the Microbiomementioning
confidence: 99%